Religion and War Resistance in the Plowshares Movement - Nepstad, Sharon Erickson (Cambridge University Press, 2013)
As the nuclear arms race exploded in the 1980s, a group of U.S. religious pacifists used radical nonviolence to intervene. Armed with hammers, they broke into military facilities to pound on missiles and pour blood on bombers, enacting the prophet Isaiah’s vision: “Nations shall beat their swords into plowshares and their spears into pruning hooks.” Calling themselves the Plowshares movement, these controversial activists received long prison sentences; nonetheless, their movement grew and expanded to Europe and Australia. In Religion and War Resistance in the Plowshares Movement, Sharon Erickson Nepstad documents the emergence and international diffusion of this unique form of high-risk collective action. Drawing on in-depth interviews, original survey research, and archival data, Nepstad explains why some Plowshares groups have persisted over time while others have floundered or collapsed. Comparing the U.S. movement with less successful Plowshares groups overseas, Nepstad reveals how decisions about leadership, organization, retention, and cultural adaptations influence movements’ long-term trajectories.